Connection and Collaboration in Global Higher Education Research - Schendel, Rebecca; Knobel, Marcelo (International Higher Education, 2024)
The field of higher education has reached a moment of maturity, having moved from the fringes of other scholarly communities to becoming a well-established field in its own right. However, despite collectively “knowing” more than ever about higher education, in practical terms, higher education is in crisis in much of the world. Increased collaboration is required in order to overcome the collective inability of the field to translate research findings into policy and practical impact.